Mejora del control operacional a través de la implementación de procedimientos específicos para servicios de conservación vial en Conalvías Construcciones S.A.C. - Guillen Sevilla, Patricia Karim (2020)
Conalvias Construcciones S.A.C. is a company in the construction sector that decided to develop the project "Improvement of operational control through the implementation of specific procedures for road conservation services" in its Consorcio Abra Toccto Project and replicate in all its road conservation contracts. The reason for the start of the project was the identification of a problem that was repeated every month, the breach of the indicator "Measurement of service levels", this indicator measures the percentage of penalties that the client applies for the breach in the execution of routine maintenance activities. The goal is not to pass 2% of penalties with respect to the total billing of the month and it was the case that the measurements of several consecutive months were well above 2%. The following tools were used to identify the causes that caused the non- compliance of the indicator: Cause Effect Diagram (Ishikawa), Tree Diagram, The 5 Why's; To find out which activities cause the greatest negative effect on service level measurement inspections, the Pareto Diagram tool was used. With the results of the tools used, the project was developed and was a success, since what was expected was obtained by considerably reducing the penalties and thus improving the measurements of the service level indicator.